Coronavirus disease 2019 in patients with rheumatic immune-mediated diseases in a single University Hospital, matched case-control study and literature review - Martínez-López, David; Ferraz-Amaro, Ivan; Prieto-Peña, Diana; Sánchez-Bilbao, Lara; Herrero-Morant, Alba; Álvarez-Reguera, Carmen; Benavides-Villanueva, Fabricio; Corrales-Selaya, Cristina; Trigueros-Vázquez, Martín; González-Gay, Miguel Ángel; Blanco, Ricardo (Frontiers in Medicine, 2022)
Background COVID-19 may present different degrees of severity. Viral infections in patients with rheumatic inflammatory diseases (R-IMID) trend to present more severe disease. However, data comparing the severity of the disease between R-IMID and the general population are scarce. Objectives To compare predisposing factors, clinical, serological features, and severity of COVID-19 infection in patients with and without R-IMID. Methods Case-control study in a single University Hospital. We included all consecutive patients with a diagnosis of an R-IMID and COVID-19 infection up to March 31st, 2021. This cohort was compared to patients without R-IMID and not receiving immunosuppressive therapy, matched for sex and age (±5 years). Confirmed infection was defined if a patient had a positive nasopharyngeal swab for SARS-CoV-2. Severity was divided into mild, moderate, severe and critical according to the United States National Institute of Health (NIH) guidelines. Results We included 274 R-IMID patients (185 women/89 men), mean age 59.1 ± 18 years. More frequent R-IMID were: Rheumatoid arthritis (28.8%), Psoriatic Arthritis (20.1%), axial Spondyloarthritis (12.4%), Polymyalgia Rheumatica (8%) and Systemic Lupus Erythematosus (8%). Hypertension and dyslipidemia were more frequent in patients with R-IMID. Although most of the cases were mild, critical cases and deaths were more frequent in R-IMID. When adjusted by comorbidities, no statistical differences were observed. Conclusion R-IMID have a very similar clinical presentation when compared to the general population. There is a trend to an increased severity of the disease in patients with R-IMID.